Tools and equipment used in the maintenance of Tanjung Emas Recreational Park / Muhammad Zaki Md Sood - Md Sood, Muhammad Zaki (2012)
Functions and Roles of Recreation Park is a place to rest / peace of mind, get away from busy area, especially in the city as a place to play / work towards a vibrant and healthy society, as a friendly conversation between individuals, neighbours, and for good loving foster family towards happy, for the greening / beautification of the environment, create ambience. Recreation is a very important element in human life to carry out recreational activities to take care of themselves. Therefore, recreation should always be well maintained to preserve the parks function. Maintenance of parks is a management and technical activities for developing and maintaining the recreation function. As a result of the review of literature several authors previously found that the level and quality of management and maintenance of parks in Malaysia is still low. The problems of tools and equipment provided to maintain the Recreational Park are mostly about the suitability, quantity and quality of tools and equipment. The objective is to identify available of the common tools and equipment used for the maintenance works of the Recreational Park, to identify the effectiveness of the use of tools and equipment for the maintenance of Recreation park, to recommend the suitable equipment and tools for the maintenance of Recreational park. Tanjung Emas Recreational Park, Muar (Johor) was selected as the study area due to the many complaints received by the Majlis Perbandaran Muar (MPM). The data obtained through observation, interviews and questionnaires of the officers and staff council and users who frequent the parks. The findings of this study have found that management and recreational park tools/ equipment used for maintenance operations under the local authorities are still moderate.